Effects of L-tryptophan, Fructan, and Casein on Reducing Ammonia, Hydrogen Sulfide, and Skatole in Fermented Swine Manure - Q. K. Sheng; Z. J. Yang; H. B. Zhao; X. L. Wang; J. F. Guo (Asian-Australasian Journal of Animal Sciences, 2015)
The effects of daily dietary Bacillus subtilis (Bs), and adding L-tryptophan, fructan, or casein to fecal fermentation broths were investigated as means to reduce the production of noxious gas during manure fermentation caused by ammonia, hydrogen sulfide (H2S), and 3-methylindole (skatole). Eighty swine (50.0±0.5 kg) were equally apportioned to an experimental group given Bs in daily feed, or a control group without Bs. After 6 weeks, fresh manure was collected from both groups for fermentation studies using a 3×3 orthogonal array, in which tryptophan, casein, and fructan were added at various concentrations. After fermentation, the ammonia, H2S, L-tryptophan, skatole, and microflora were measured. In both groups, L-tryptophan was the principle additive increasing skatole production, with significant correlation (r = 0.9992). L-tryptophan had no effect on the production of ammonia, H2S, or skatole in animals fed Bs. In both groups, fructan was the principle additive that reduced H2S production (r = 0.9981). Fructan and Bs significantly interacted in H2S production (p = 0.014). Casein was the principle additive affecting the concentration of ammonia, only in the control group. Casein and Bs significantly interacted in ammonia production (p = 0.039). The predominant bacteria were Bacillus spp. CWBI B1434 (26%) in the control group, and Streptococcus alactolyticus AF201899 (36%) in the experimental group. In summary, daily dietary Bs reduced ammonia production during fecal fermentation. Lessening L-tryptophan and increasing fructan in the fermentation broth reduced skatole and H2S.